2000
DOI: 10.1021/ja002602o
|View full text |Cite
|
Sign up to set email alerts
|

Novel α-Amino Acid-Based Hydroxamic Acid Ligands for Vanadium-Catalyzed Asymmetric Epoxidation of Allylic Alcohols

Abstract: Novel α-Amino Acid-Based Hydroxamic Acid Ligands for VanadiumCatalyzed Asymmetric Epoxidation of Allylic Alcohols.-A novel class of chiral ligands for the vanadium-catalyzed asymmetric epoxidation of allylic alcohols, namely α-amino acid-based hydroxamic acid derivatives, is tested. Optimization regarding the amino acid side chain, the N-protecting group and the diarylmethyl group shows that best results are obtained for NTDH. A variety of mono-and disubstituted allylic alcohols are epoxidized with moderate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 7 publications
0
61
0
Order By: Relevance
“…Furthermore, certain studies have tried to unravel the initial steps in the reaction of VO(acac) 2 with TBHP [7,8]. The active intermediates were widely accepted to be vanadium(+V) alkylperoxo complexes in the VO(acac) 2 /TBHP [4,16,17,22] and VO(acac) 2 /TBHP/ligand [24][25][26][27][28] catalytic systems. More specifically, Talsi et al [8] investigated the role of alkylperoxo complexes for the cyclohexene epoxidation with organic hydroperoxides in presence of VO(acac) 2 in detail by NMR and EPR.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain studies have tried to unravel the initial steps in the reaction of VO(acac) 2 with TBHP [7,8]. The active intermediates were widely accepted to be vanadium(+V) alkylperoxo complexes in the VO(acac) 2 /TBHP [4,16,17,22] and VO(acac) 2 /TBHP/ligand [24][25][26][27][28] catalytic systems. More specifically, Talsi et al [8] investigated the role of alkylperoxo complexes for the cyclohexene epoxidation with organic hydroperoxides in presence of VO(acac) 2 in detail by NMR and EPR.…”
Section: Introductionmentioning
confidence: 99%
“…Although in terms of enantioselectivities is less efficient than the bis-hydroxamic ligand-based systems reported by Yamamoto [35,37], this system exhibits a high reactivity even comparable to that of VO(acac) 2 alone. The observed accelerating effect of the ligand was attributed to the presence of hydrogen bonds between the sulfonamide group and the incoming allylic alcohol that tether the two reactants together.…”
Section: Fig 14mentioning
confidence: 65%
“…Vanadium is less moisture sensitive than titanium and permitted procedures with lower catalyst loading. After the pioneering work of Sharpless, who reported enantioselectivities up to 80% using a proline-based hydroxamic acid [34], another important achievement was reported by Yamamoto and coworkers in 2000 [35]. They designed a new chiral hydroxamic acid derived from tert-leucine [24-30]. able to afford good enantioselectivities in the epoxidation of disubstituted allylic alcohols in reasonable reaction times with only 1% catalyst loading and TBHP as oxidant.…”
Section: Epoxidationsmentioning
confidence: 99%
“…[11][12][13] These ligands were demonstrated to be effective for the vanadium-catalyzed asymmetric epoxidation of allylic and homoallylic alcohols (Scheme 2). These results suggested that several structural features of the hydroxamic acid were very suitable to generate reactive complex with vanadium and the complex significantly enhanced the enantioselectivities of the epoxy alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ligand deceleration effect was still observed in these cases. 11,12,14 To exclude this effect, we planned to design a new C 2 -symmetric BHA incorporating several features: 1) with an additional binding site, 3 is capable of chelating as an bi-dentate ligand to the metal center to complete the generation of chiral vanadium-ligand complex more efficiently than monohydroxamic acid 1 and 2; 2) when the R group of amide in 3 is sufficiently large, it will direct the amide carbonyl oxygen towards the cyclohexane ring to minimize steric interaction and restrict its coordination with the metal. A second aspect is that the attachment of additional ligands to vanadium will also be restricted for steric reasons.…”
Section: Resultsmentioning
confidence: 99%